Update of the hypotheses of the etiology of anomalous left coronary artery from the pulmonary artery (ALCAPA) - Bolaños-Hernández, Manuel Alejandro (2021)
Anomalous left coronary artery from the pulmonary artery(ALCAPA) is a rare cardiac malformation that consists of the anomalous origin of the left coronary artery from the pulmonary artery. Before its first description in 1933, various hypotheses about its embryonic origin had already begun to be proposed, starting with Hbnkossof in 1911, then Hackensellner in 1956 and finally Bogers in 1988, the first two hypotheses are incongruous with cardiac embryology, on the other hand Bogers take is the most accepted at present, which explains that it is due to an incorrect alignment of the myocardial tissue to the pulmonary artery trunk would cause the anomalous origin of the coronary arteries, thanks to advances in the field of molecular study, the fundamental role played by the ligand CXCL12 and its respective receptor CXCR4 in the origin of the coronary arteries has been found to play a very important role, CXCL12 is secreted by the cells of the wall aortic and plays a chemoattractant role towards CXCR4-positive peritroncal endothelial cells for to guide migration and subsequent penetration into the aorta, therefore a mutation in CXCL12 or CXCR4 could be responsible for the misalignment of myocardial tissue described by Bogers, which leads to abnormal development of ACs. The objective of the study is to carry out an updated review on the different theories of the embryological origin and molecular bases of ALCAPA. A literature realize in the databases of MedLine (PubMed), Access Medicina, Clinical Key and Science Direct about the ALCAPA congenital anomaly, obtaining 50 articles after their selection process.